Analyses on long-term behavior of composite steel–concrete beams with weak interface using a state space approach. (15th March 2021) - Zhang, He; Quan, Liwei; Wang, Li; Wu, Jinxin; Zhang, Zhicheng
Highlights: Time-dependent behavior of steel-concrete composite beams with weak interface is analyzed. The deflection, slippage, and resultant forces are solved simultaneously with state space method. Effects of shrinkage, creep, and interfacial slippage are investigated. Abstract: The structural behavior of concrete-steel composite beam applied to long-term load is influenced by the creep and shrinkage of concrete slab. To investigate this phenomenon, the state space method is adopted in the paper to derive the inner forces and analytical solutions of interfacial shear force and slip. The numerical formula is derived from basic mechanical differential equations considering the force equilibrium and strain compatibility at each node. The slip between steel beam and concrete slab can be represented by governing equations, with the assumption of linear load–slip relation. Then, the redistribution of stress between concrete slab and the steel beam and the increment of deflections as a result of creep and shrinkage of concrete slab are investigated in the paper. The numerical model can be applied successfully in simulating the time-dependent structural behavior of multi-span continuous beam in spite of load type. Lastly, the validity of the numerical model is established by some correlation studies between analytical and numerical results and several parameter studies.